Pengaruh E-Learning Menggunakan Quipper School Terhadap Kemandirian Belajar dan Hasil Belajar Siswa SMP Pada Pelajaran Matematika - Rita Perawati; Hepsi Nindiasari; Syamsuri Syamsuri (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2020)
The low independence of student learning is due to students being bored with learning the lack of innovation of teachers in using learning media, and it is predicted that E-Learning using Quipper School can help students improve student learning independence and learning outcomes. This study aims to analyze the effect of E-Learning using Quipper School on learning independence and junior high school student learning outcomes in mathematics. This study used a quasi-experimental method with a pretest and posttest nonequivallent control group design. The population in this study were all students of SMPI Al Azhar 11 Serang, Serang City, Prov. Banten and the sample were selected by purposive sampling in order to obtain 3 classes, namely the Bilingual class, Tahfidz and Regular as the experimental class. To obtain research data, instruments were used in the form of a learning outcome ability test and a student learning independence questionnaire. The analysis shows that: 1) There are differences in the learning independence of Bilingual, Tahfidz and Regular students with E-Learning using Quipper School, 2) There are differences in student learning outcomes in Bilingual, Tahfidz and Regular classes with E-Learning using Quipper School.